P032 Does Patient Knowledge Affect Anxiety, Depression, and Quality of Life in Patients With Inflammatory Bowel Disease?. (December 2019) - Hosni, Mohammad; Hamade, Aya; ElKhoury, Habib; Kfouri, Jad; Chahrour, Mohamad; Kahlifeh, Joanna; Saadeh, Serena; Kattouf, Nadim; Sharara, Alaa; Francis, Fadi; Mourad, Fadi; Soweid, Assaad; et al.
Abstract : BACKGROUND: Disease specific knowledge amongst inflammatory bowel disease (IBD) patients remains lacking. Our study aims to (1) determine the extent of disease specific knowledge amongst IBD patients in Lebanon and (2) determine the impact of patient knowledge on anxiety, depression, and quality life while controlling for disease activity. METHODS: We prospectively recruited adult IBD patients from the GI clinic at a tertiary referral center in Beirut, Lebanon. Demographic data was collected and patients were asked to fill the following questionnaires: (1) Short IBD Questionnaire (SIBDQ) as a measure of quality of life (QoL), (2) Harvey-Bradshaw Index (HBI) for Crohn's disease (CD) or Ulcerative Colitis (UC) Activity Index (UCAI) for UC patients as a measure of disease activity, (3) Hospital Anxiety and Depression Scale (HADS), as a measure for anxiety and depression, and (4) the Crohn's and Colitis Knowledge (CCKnow) questionnaire as a measure of IBD-specific patient knowledge. Pearson Chi-square, student's t-test and multivariate analysis was used for statistical analyses. RESULTS: A total of 95 patients were included; 55.8% males, 18–65 years of age, mean age 34.5 years ± 12.0. Over half (53.7%) of patients had CD, 44.2% UC, and 2.1% IBD-unclassified. The majority of patients (51.6%) were unmarried and had a university degree (77.9%). The mean CCKnow score amongst patients was 8 ± 4, with 53.7% scoring ≥8. Of all patients, 43.2% had anxiety, 22.1% had depression, mean SIBDQ score was 49 ± 15, with 49.5% having a poor QoL. The 51 CD patients had a mean CCKnow of 8 ± 4, with 45.1% scoring ≥8. These patients had a mean HBI of 5 ± 4. The 29 UC patients had a mean CCKnow of 9 ± 4, with 61.9% scoring ≥8. The mean UCAI for these patients was 5 ± 4. Patients with a university degree had more disease specific knowledge (CCKnow score ≥8). Comparing patients with CCKNOW ≥ 8 to those who lack disease specific knowledge, there was no significant difference in anxiety, depression or quality of life. When analyzing per IBD subtype, CD patients who had more disease specific knowledge had a tendency to be more anxious and depressed. After controlling for disease activity, gender, level of education, age, and years of disease, patients who were considered knowledgeable regarding their disease had no association with any of the following outcomes in the UC population: anxiety, depression, or quality of life; however, being female with CD was associated with increased levels of anxiety. CONCLUSION(S): IBD patients in Lebanon knew less about their IBD compared to values reported in the literature. There were no differences between patients who knew about their disease compared to those who do not except for a trend towards significance in anxiety amongst CD patients who knew more about their disease.